Mechanical properties and lattice misfit of γ/γ' strengthened Co-base superalloys in the Co-W-Al-Ti quaternary system - Zenk, Christopher; Neumeier, Steffen; Stone, H. J.; Göken, Mathias (Intermetallics, 2014)
A continuous γ/γ' two-phase field has been identified extending between the ternary Co-Al-W system to the binary Co-Ti system. The lattice misfits of two phase γ/γ' alloys from the Co-Al-W-Ti quaternary system were measured by X-ray diffraction and found to be positive and vary linearly with composition. Differential scanning calorimetry measurements showed that the solidus and liquidus temperatures decrease from the W and Al rich end to the Ti rich end, whilst the γ' solvus temperature increases. Long term heat treatments identified the occurrence of discontinuous precipitation at the grain boundaries in many of the alloys studied. The high temperature strength and creep resistance of the quaternary alloys in the intermediate composition range surpassed those of the binary and ternary alloys. © 2014 Elsevier Ltd. All rights reserve
Keywords: B. Age-hardening; B. Thermal stability; B. Yield stress; D. Microstructure; F. Differential scanning calorimetry; F. Diffraction/sacterring (electron; neutron and X-ray)